Palbociclib for Residual High-Risk Invasive HR-Positive and HER2-Negative Early Breast Cancer—The Penelope-B Trial. Issue 14 (10th May 2021) - Loibl, Sibylle; Marmé, Frederik; Martin, Miguel; Untch, Michael; Bonnefoi, Hervé; Kim, Sung-Bae; Bear, Harry; McCarthy, Nicole; Melé Olivé, Mireia; Gelmon, Karen; García-Sáenz, José; Kelly, Catherine M.; et al.
Abstract : PURPOSE: About one third of patients with hormone receptor–positive, human epidermal growth factor receptor 2–negative breast cancer who have residual invasive disease after neoadjuvant chemotherapy (NACT) will relapse. Thus, additional therapy is needed. Palbociclib is a cyclin-dependent kinase 4 and 6 inhibitor demonstrating efficacy in the metastatic setting. PATIENTS AND METHODS: PENELOPE-B (NCT01864746 ) is a double-blind, placebo‐controlled, phase III study in women with hormone receptor–positive, human epidermal growth factor receptor 2–negative primary breast cancer without a pathological complete response after taxane‐containing NACT and at high risk of relapse (clinical pathological staging-estrogen receptor grading score ≥ 3 or 2 and ypN+). Patients were randomly assigned (1:1) to receive 13 cycles of palbociclib 125 mg once daily or placebo on days 1-21 in a 28-day cycle in addition to endocrine therapy (ET). Primary end point is invasive disease-free survival (iDFS). Final analysis was planned after 290 iDFS events with a two-sided efficacy boundary P < .0463 because of two interim analyses. RESULTS: One thousand two hundred fifty patients were randomly assigned. The median age was 49.0 years (range, 19-79), and the majority were ypN+ with Ki-67 ≤ 15%; 59.4% of patients had a clinical pathological staging-estrogen receptor grading score ≥ 3. 50.1% received aromatase inhibitor, and 33% of premenopausal women received a luteinizing hormone releasing hormone analog in addition to either tamoxifen or an aromatase inhibitor. After a median follow-up of 42.8 months (92% complete), 308 events were confirmed. Palbociclib did not improve iDFS versus placebo added to ET-stratified hazard ratio, 0.93 (95% repeated CI, 0.74 to 1.17) and two-sided weighted log-rank test (Cui, Hung, and Wang) P = .525. There was no difference among the subgroups. Most common related serious adverse events were infections and vascular disorders in 113 (9.1%) patients with no difference between the treatment arms. Eight fatal serious adverse events (two palbociclib and six placebo) were reported. CONCLUSION: Palbociclib for 1 year in addition to ET did not improve iDFS in women with residual invasive disease after NACT.